2018
DOI: 10.1007/s11571-018-9500-6
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related changes of EEG synchronization during a visual working memory task

Abstract: Differences of EEG synchronization between normal old and young people during a working memory (WM) task were investigated. The synchronization likelihood (SL) is a novel method to assessed synchronization in multivariate time series for non-stationary systems. To evaluate this method to study the mechanisms of WM, we calculated the SL values in brain electrical activity for both resting state and task state. EEG signals were recorded from 14 young adults and 12 old adults during two different states, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Activity-dependent plasticity and LTP-like plasticity after motor learning are reduced in older individuals (Zimerman et al, 2013;Ghasemian-Shirvan et al, 2020). A previous study reported EEG findings indicating attention deficits during visual memory tasks in older people (Teng et al, 2018). In addition to the effect of aging, stroke induces structural and functional changes in the brain, resulting in decreased motor cortical activation.…”
Section: Discussionmentioning
confidence: 95%
“…Activity-dependent plasticity and LTP-like plasticity after motor learning are reduced in older individuals (Zimerman et al, 2013;Ghasemian-Shirvan et al, 2020). A previous study reported EEG findings indicating attention deficits during visual memory tasks in older people (Teng et al, 2018). In addition to the effect of aging, stroke induces structural and functional changes in the brain, resulting in decreased motor cortical activation.…”
Section: Discussionmentioning
confidence: 95%
“…Beta band activity plays a vital role in inter-neuronal communication in functional networks in working memory [ 72 ]. The beta band is associated with attention deficiency in elderly individuals in terms of working memory [ 73 , 74 ], and task-evoked alterations were observed in a beta band network topology [ 43 , 73 ]. A recent study suggested that age-related alterations in EEG network connectivity are correlated with age-related slowing in attention tasks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to conduct more in-depth analyses of individual variables such as neuropsychological test scores and demographic characteristics as potentially mediating factors that account for age-related differential patterns of activated brain networks. From the perspective of utilizing multiple EEG characteristics, we suggest that researchers consider employing the power spectral density and functional connectivity (Ewald et al, 2012;Teng et al, 2018;Packard et al, 2020) in addition to the specific component of ERP that we focused on in this study to explore the underlying cognitive mechanisms associated with the aged brain in more detail. Despite some limitations of the study, it has great importance in that it demonstrated that our task paradigm is effective at revealing the aging effects…”
Section: Discussionmentioning
confidence: 99%